Comparison of Cord Osteosynthesis Versus Standard Osteosynthesis for Treating Hand Bone Fractures in the Kyrgyz Republic: A Retrospective Study (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Whole-body computed tomography (WBCT) can be challenging in identifying extremity injuries dueto variations in pain tolerance, other injuries, and examination quality. It is advised to conduct a clinical examinationand image review after the patient has stabilized or regained consciousness. Although prompt treatment of limbfractures is crucial, WBCT poses challenges, including incorrect positioning, artifacts, and accurate thin-sectioncomputed tomography interpretation. Hand and wrist reconstruction can be complicated, especially when multipleinjuries are present. This study aimed to analyze the composition of hand bone fractures in the Kyrgyz Republicand evaluate the effectiveness of cord osteosynthesis compared with alternative procedures for fixing hand bones.Materials and Methods: This retrospective study analyzed data from patients at the National Hospital of theMinistry of Health’s Hand Microsurgery Department in the Kyrgyz Republic from 2018 to 2023. The inclusioncriteria were patients aged 18–65 with a confirmed wrist fracture diagnosis, informed consent, and no significanthealth issues. The 90 patients who underwent cord osteosynthesis comprised Group 1, while Group 2, consisting of34 patients, underwent standard osteosynthesis. Results: The study found that the mean age of patients in Group 1was 23.3 ± 1.8 years, while Group 2 had a mean age of 34.3 ± 3.0 years. The mean hospital stay for patients inGroup 1 was 6.11 days, while patients in Group 2 had a mean hospital stay of 10.35 days. The mean systolic bloodpressure in Group 1 was 108.2 ± 1.4 mmHg, while in Group 2, the mean systolic BP was 115.5 ± 2.4 mmHg. Thedifference between the two groups was statistically significant (P = 0.009). Conclusion: The findings suggest thatcord osteosynthesis may be more effective in treating hand bone fractures than the standard approach.